Effect of intravitreal ranibizumab on serous retinal detachment in branch retinal vein occlusion - Dogan E (Dove Medical Press, 2018)
Emine Dogan,1 Ozkan Sever,2 Burcin Köklü Çakir,1 Erkan Celik1 1Department of Ophthalmology, Sakarya University Medical Education and Research Hospital, Sakarya, Turkey; 2Department of Ophthalmology, Namik Kemal University School of Medicine, Namik Kemal University, Tekirdag, Turkey Purpose: The aim of this study was to evaluate the effect of initial intravitreal ranibizumab injection on visual acuity (VA) and central macular thickness (CMT) for the treatment of macular edema (ME) with and without serous retinal detachment (SRD) secondary to branch retinal vein occlusion (BRVO). Materials and methods: Fifty-two BRVO eyes, treated with intravitreal ranibizumab injection for ME with and without SRD, were retrospectively reviewed. Patients were divided into two groups according to spectral domain optical coherence tomography (SD-OCT). The efficacy of intravitreal ranibizumab injection at first month was assessed by analyzing the change in best-corrected VA and reduction in CMT with SD-OCT. Results: There were 21 patients with SRD and 31 patients with only CME (no-SRD). CMT was significantly greater in the SRD group than in the CME group (451±62.2 µm vs 383.5±37.2 µm, respectively, P<0.05). After initial intravitreal ranibizumab injection, mean VA improved from 0.87±0.26 logarithm of the minimum angle of resolution (LogMAR) to 0.54±0.27 LogMAR (P<0.01) and CMT decreased from 451±62.2 µm to 379.3±58.6 µm (P<0.001) in the SRD group. In the no-SRD group, mean VA improved from 0.69±0.25 LogMAR to 0.44±0.25 LogMAR (P<0.001) and the CMT decreased from 383.5±37.2 µm to 337.7±39.4 µm (P<0.001) at the first month visit. Eyes with SRD revealed better anatomic results and greater reduction of CMT after intravitreal ranibizumab injection (P<0.01). Conclusion: VA and CMT can be improved by intravitreal ranibizumab injection in BRVO patients with and without SRD. However, more marked improvement in macular morphology was achieved in patients with SRD than those without SRD. Keywords: ranibizumab, vein occlusion, serous detachment